Recruitment of inflammatory monocytes after liver transplantation and correlation with clinical outcome. (23rd February 2017) - Robertson, Francis; Male, Victoria; Wright, Graham; Fuller, Barry; Davidson, Brian
Abstract: Background: Ischaemia reperfusion injury is a key cause of mortality and graft loss after liver transplantation. After tissue injury, monocytes are rapidly mobilised and recruited to injured tissue by monocyte chemoattractant protein-1 (MCP-1). Elevated MCP-1 concentrations correlate with poorer outcomes in patients after haemorrhagic stroke but have not been evaluated as a prognostic marker in clinical liver transplantation. We aimed to assess the role of inflammatory monocytes and MCP-1 in ischaemia reperfusion injury Methods: Adult patients undergoing liver transplantation at the Royal Free Hospital, London, UK, were recruited. Liver biopsy samples were collected preimplantation and 2 h after reperfusion from five patients. Intrahepatic mononuclear cells were extracted for immediate analysis by flow cytometery. Plasma MCP-1 concentrations from 33 patients were measured preoperatively by ELISA, 2 h and 24 h after reperfusion, and correlated with graft function by measurement of day 3 aspartate aminotransferase (AST) and early allograft dysfunction (EAD) score. Findings: Flow cytometric analysis demonstrated an increase in mean classical monocytes after reperfusion compared with preimplantation (4·18% of total live cells [SD 2·61] vs 0·61 [0·38], p=0·018). In three of the five recipients we distinguished cells of donor versus recipient origin by HLA-A allele expression to demonstrate that 88% (6·24) of the classical monocytes were recipient derived in the postreperfusion biopsy sample. Median MCP-1 concentrations were significantly raised after reperfusion (385·61 pg/mL [IQR 244·75–715·20] vs 71·2 [55·61–113·99], p<0·0001) and had reduced to 740·61 (38·46–133·71) within 24 h. Patients with EAD (n=17) had significantly higher MCP-1 concentrations at 24 h than those without EAD (74·82 [66·69–219·93] vs 47·44 [29·53–77·73], p=0·037). MCP-1 concentrations at 24 h correlated with day 3 AST concentrations (p=0·002). Interpretation: Our results show that classical monocytes are rapidly recruited to the liver after ischaemia reperfusion injury, and that high MCP-1 concentrations at 24 h are associated with poorer graft function. Therefore, MCP-1 blockade presents an attractive strategy to reduce graft ischaemia reperfusion injury. Funding: None.